Characteristics That Influence the Success of External Cephalic Version in Nulliparous Women [A198]. (May 2022) - Gude, Jessica; Anasti, James; Durgham, Ryan A.
Abstract : INTRODUCTION: Studies identified that nulliparous women (NW) are at increased risk for failed external cephalic version (ECV). This study examined maternal characteristics and maternal/neonatal outcomes of NW with failed and successful ECVs. METHODS: Using the NBER Natality Database (2016–2018) ECV attempts in NW were identified. ECV success and cesarean delivery (CD) rates were calculated. Maternal demographics, comorbidities, and neonatal outcomes were compared between cohorts using bivariate analysis. Statistically significant ( P <.001) differences were reported. RESULTS: The ECV success rate in 13, 015 NW was 40.0%. Black NW had the highest success rate (54.5%), followed by Hispanic (49.1%), Asian/Pacific Islander (45.0%), White (37.8%), and American Indian/Alaskan Native (27.2%) NW. Self-pay NW had the highest ECV success rate (58.3%), followed by Medicaid (45.2%), and private insurance (26.8%). Successful ECV saw decreased neonatal ventilation (5.4% versus 6.8%) but increased NICU admission (9.9% versus 6.7%). NW with successful ECV had a 29.9% CD rate. Higher CD rates were found in NW with a history of hypertension (54.3% versus 29.4%), gestational diabetes mellitus (56.3% versus 28.9%), and gestational hypertension (38.3% versus 29.2%). There was no association between race or payer status and CD rate after successful ECV. Pertinent negatives for both cohorts include, age, BMI, history of diabetes, birth weight, gestational age at birth, Apgar scores, neonatal seizures, maternal ICU admission, transfusion, and unplanned hysterectomy. CONCLUSION: When counseling NW on ECV, it is important to fully account for several factors that affect the chance of ECV success or CD. The reasons for the impact of the factors found here will require further investigation.